PARTISIPASI PEMILIH DIPENGARUHI KURANGNYA MINAT POLITIK DAN KETIDAKPUASAN DENGAN PILIHAN KANDIDAT PADA GENERASI XYZ DI KABUPATEN BANDUNG BARAT - Ito Turyadi (Universitas 17 Agustus 1945 Semarang, 2022)
This article was written based on the manifestation of researcher participation in the democratic system in Indonesia, especially in West Bandung Regency. This study aims to determine the voter turnout of 3 generations (generation X, generation Y, and generation Z) from the perspective of lack of political interest and dissatisfaction with the candidates. This research uses descriptive and verification methods with a quantitative approach, with a total sample of 145 respondents spread from 3 villages (Ciwaruga Village, Cigugur Girang Village and Cihanjuang Village). The research location is the area with the largest population and voting rights in the Parongpong District, West Bandung. Methods of data analysis using path analysis using SPSS software. The results of the study show that the total influence of ignorance or lack of political interest and dissatisfaction with the choice of candidates on voter participation in generation X is indicated by the magnitude of the coefficient of determination (r2) = 0.488 or 48.8%, in generation Y is indicated by the magnitude of the coefficient of determination (r2) ) = 0.580 or 58%, in generation Z it is shown by the magnitude of the coefficient of determination (r2) = 0.793 or 79.3%. So it was concluded that the model formed was included in the strong category, so that in this study the variables of ignorance or lack of political interest and dissatisfaction with the choice of the right candidate were used to measure voter turnout in Parongpong District, West Bandung.